Identity Negotiation in the Age of Global Migration in Exophonic Novels (NOBEL: Journal of Literature and Language Teaching, 2021)
The vast changing of the cultural structure caused by globalization and migration has a complicated identity. A higher number of migrants from numerous parts of the world has arisen lately, especially from Middle Eastern and Muslim countries facing various conflicts. Negotiating identities, thus, becomes inevitable, particularly for migrants. Identity negotiation has been frequently raised as an underlying issue in early 2000s literary works. Such an era becomes a worth researching topic on migration as portrayed in exophonic novels. Exophony refers to writing and producing literary works in a language that is not one’s mother tongue. The article covers the analysis of novels written by exophonic writers: Khaled Hosseini’s The Kite Runner (2003), Elif Shafak’s The Bastard of Istanbul (2006), and Mohsin Hamid’s The Reluctant Fundamentalist (2007). The analysis focuses on identity negotiation experienced by Muslim diaspora characters by employing Homi K. Bhabha’s cultural identity. This study reveals that identity negotiation often occurs in the context of power relations and can occasionally be hegemonizing. This notion is backed by the fact that the complexity of the identity negotiation process occurs not only at the intersection of opposed cultures or civilizations but also at the intersection of politics and power relations.